Urban Space Reconstruction under the Influence of Enlightenment Thought - Ahmed, Shaik Mujeeb; Aldhebaiei, Khawla; Alawadhi, Majedah Ahmed (Journal of Progress in Civil Engineering, 2025)
The city of Zacatecas, founded in the 16th century and with its unique characteristics of a city without a Renaissance layout, rather a mining city that grew along the course of the stream and the mining benefits, was part of the broader project to explore the mines in northern New Spain. Although it is true that throughout the 16th and 17th centuries architectural spaces were built that defined the physiognomy of the city, we locate a first modern urban transformation at the end of the 18th century, with the so - called Bourbon reforms, and their urban planning project. The first two intendants carried out some urban interventions, which contributed to urban reorganization, the most important of them was the division of the city into quarters, a measure that contributed to having a better social and population control of the city. Some new spaces were projected redefining the city. We have the project for the grain warehouse, which was able to be carried out at the end of the 18th century due to the pressing needs for grain storage, but for various reasons the building was unable to fulfil the function for which it was intended. The layout of the Alameda was planned so that the city would have a recreational space for the inhabitants of the 18th century, however, despite the opposition of many sectors of the population, it was frowned upon by society. Talking about the history, culture and art of the city of Zacatecas means referring to what we consider to be three stages of urban transformation throughout its history. In this sense, we will focus on three moments in the history of the city that underwent transformations that influenced urban morphology, which means moving away from other moments, projects and social actors that intervened in the physiognomy of the historic city. This study sheds light on how Enlightenment ideals shaped urban governance and spatial arrangements, providing valuable insights into the historical evolution of modern urban planning.